Peritumoral adipose tissue promotes lipolysis and white adipocytes browning by paracrine action - Pagnotta, Priscila; Gantov, Mariana; Fletcher, Sabrina; Lombardi, Antonella; Crosbie, María Lujan; Santiso, Natalia; Ursino, Anabela; Frascarolli, Celeste; Amato, Alicia; Dreszman, Rubén; Calvo, Juan Carlos; Toneatto, Judith (Frontiers in Endocrinology, 2023)
Background Stromal adipocytes and tumor breast epithelial cells undergo a mutual metabolic adaptation within tumor microenvironment. Therefore, browning and lipolysis occur in cancer associated adipocytes (CAA). However, the paracrine effects of CAA on lipid metabolism and microenvironment remodeling remain poorly understood. Methods To analyze these changes, we evaluated the effects of factors in conditioned media (CM) derived from explants of human breast adipose tissue from tumor (hATT) or normal (hATN) on morphology, degree of browning, the levels of adiposity, maturity, and lipolytic-related markers in 3T3-L1 white adipocytes by Western blot, indirect immunofluorescence and lipolytic assay. We analyzed subcellular localization of UCP1, perilipin 1 (Plin1), HSL and ATGL in adipocytes incubated with different CM by indirect immunofluorescence. Additionally, we evaluated changes in adipocyte intracellular signal pathways. Results We found that adipocytes incubated with hATT-CM displayed characteristics that morphologically resembled beige/brown adipocytes with smaller cell size and higher number of small and micro lipid droplets (LDs), with less triglyceride content. Both, hATT-CM and hATN-CM, increased Pref-1, C/EBPβ LIP/LAP ratio, PPARγ, and caveolin 1 expression in white adipocytes. UCP1, PGC1α and TOMM20 increased only in adipocytes that were treated with hATT-CM. Also, hATT-CM increased the levels of Plin1 and HSL, while decreased ATGL. hATT-CM modified the subcellular localization of the lipolytic markers, favoring their relative content around micro-LDs and induced Plin1 segregation. Furthermore, the levels of p-HSL, p-ERK and p-AKT increased in white adipocytes after incubation with hATT-CM. Conclusions In summary, these findings allow us to conclude that adipocytes attached to the tumor could induce white adipocyte browning and increase lipolysis as a means for endocrine/paracrine signaling. Thus, adipocytes from the tumor microenvironment exhibit an activated phenotype that could have been induced not only by secreted soluble factors from tumor cells but also by paracrine action from other adipocytes present in this microenvironment, suggesting a “domino effect”.